2017
DOI: 10.1063/1.5002180
|View full text |Cite
|
Sign up to set email alerts
|

Optically transparent solid electrodes for precision Penning traps

Abstract: We have conceived, built, and operated a cryogenic Penning trap with an electrically conducting yet optically transparent solid electrode. The trap, dedicated to spectroscopy and imaging of confined particles under large solid angles is of 'half-open' design with one open endcap and one closed endcap that mainly consists of a glass window coated with a highly transparent conductive layer. This arrangement allows for trapping of externally or internally produced particles, yields flexible access for optical exc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…[] It is a variation of a closed cylindrical Penning trap, with one closed endcap replaced by open cylindrical electrodes to allow injection and ejection of particles, and the other endcap being electrically closed while optically transparent, which in the present case is realized by a window with a conductive coating of indium tin oxide (ITO) . This special electrode arrangement has the confinement region in close proximity to the optically open endcap, and thus features a largely enhanced solid angle of detection as compared to the standard open‐endcap design . Tests have shown that highly charged ions can be confined for periods of days in this trap under well‐defined conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[] It is a variation of a closed cylindrical Penning trap, with one closed endcap replaced by open cylindrical electrodes to allow injection and ejection of particles, and the other endcap being electrically closed while optically transparent, which in the present case is realized by a window with a conductive coating of indium tin oxide (ITO) . This special electrode arrangement has the confinement region in close proximity to the optically open endcap, and thus features a largely enhanced solid angle of detection as compared to the standard open‐endcap design . Tests have shown that highly charged ions can be confined for periods of days in this trap under well‐defined conditions.…”
Section: Methodsmentioning
confidence: 99%
“…In highly charged ions, such electron magnetic moment measurements are possible in two complementary ways, either by the continuous Stern–Gerlach effect applied to ions with zero‐spin nuclei, in full similarity to the measurements, or by making use of the fact that in highly charged ions above a certain value of Z , the hyperfine structure of a few‐electron ion becomes accessible for laser spectroscopy . Here, we discuss this latter approach by the ARTEMIS experiment with highly charged ions in a cryogenic Penning trap that is optimized for optical spectroscopy under large solid angles . This experiment is located at the HITRAP facility at GSI, Germany.…”
Section: Introductionmentioning
confidence: 99%
“…ITO remains conductive and optically transparent at cryogenic temperatures. [89] Second, an additional pair of linear dummy traps is added at either side of the array. The 10 central linear traps used for the quantum register are thereby increased to 14 linear traps.…”
Section: Appendix C: Simulation Of a Linear Trap Array With 10 × 10 T...mentioning
confidence: 99%
“…By employing of a non-neutral plasma method, a linear trapping model that accounts for large ion clouds has been demonstrated which will become the core of an atomic clock [273]. A novel cryogenic Penning trap geometry, intended to perform high resolution spectroscopy and experiments and enhanced resolution imaging of levitated particles is described in [274].…”
Section: Electrodynamic Traps As Tools For Confining Ocpsmentioning
confidence: 99%